Proceedings of the Thirtieth Annual Symposium on Computational Geometry 2014
DOI: 10.1145/2582112.2582124
|View full text |Cite
|
Sign up to set email alerts
|

The limited blessing of low dimensionality

Abstract: We are studying d-dimensional geometric problems that have algorithms with 1−1/d appearing in the exponent of the running time, for example, in the form of 2 n 1−1/d or n k 1−1/d . This means that these algorithms perform somewhat better in low dimensions, but the running time is almost the same for all large values d of the dimension. Our main result is showing that for some of these problems the dependence on 1 − 1/d is best possible under a standard complexity assumption. We show that, assuming the Exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…From the perspective of treewidth and exact algorithms, unit disk graphs have some intriguing properties: they are potentially dense, (may have treewidth Ω(n)), but they still exhibit the "square root phenomenon" for several problems just as planar and minor-free graphs do; so for example one can solve I S or 3 in these classes in 2 O( √ n) time [29], while these problems would require 2 Θ(n) time in general graphs unless the Exponential Time Hypothesis (ETH) [23] fails. In R d , the best I S running time for unit ball graphs is 2 Θ(n 1−1/d ) [31,14]. Note that d-dimensional Euclidean space has bounded doubling dimension, or in other words, Euclidean space has polynomial growth: balls of radius r have volume poly(r).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of treewidth and exact algorithms, unit disk graphs have some intriguing properties: they are potentially dense, (may have treewidth Ω(n)), but they still exhibit the "square root phenomenon" for several problems just as planar and minor-free graphs do; so for example one can solve I S or 3 in these classes in 2 O( √ n) time [29], while these problems would require 2 Θ(n) time in general graphs unless the Exponential Time Hypothesis (ETH) [23] fails. In R d , the best I S running time for unit ball graphs is 2 Θ(n 1−1/d ) [31,14]. Note that d-dimensional Euclidean space has bounded doubling dimension, or in other words, Euclidean space has polynomial growth: balls of radius r have volume poly(r).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several papers studying I S , D S , H C , q C , etc. in unit ball graphs in Euclidean space [24,25,31,4,18,14], all concluding that 2 O(n 1−1/d ) is the optimal running time for these problems in R d . In this paper, we show that a similar phenomenon occurs in H d , but shifted by one dimension: the problems can be solved in 2 O( √ n) time in H 3 , just as in R 2 ;…”
Section: Introductionmentioning
confidence: 99%
“…In this problem given a set of n unit balls in R d , we seek to find a set of k pairwise non-intersecting balls. It is known that this problem can be solved in time n O(k 1−1/d ) , for any d ≥ 2 [1,19], and that there is no algorithm with running time f (k)n o(k 1−1/d ) , for any computable function f , assuming ETH [19] (see also [17]). The upper bound has been generalized for fractal dimension as follows: It has been shown that when the set of centers of the balls has fractal dimension δ, the problem can be solved in time n O(k 1−1/δ log n) [23].…”
Section: Independent Set Of Unit Ballsmentioning
confidence: 99%
“…Informally, a typical NP-hardness reduction for some geometric problem in the plane works as follows: One encodes some known computationally hard problem by constructing "gadgets" that are arranged in a grid-like fashion in R 2 (see, e.g. [19]). More generally, for problems in R d , the gadgets are arranged along some d-dimensional grid.…”
Section: From Spanner Lower Bounds To Running Time Lower Boundsmentioning
confidence: 99%
“…exact computation. Grid Tiling has also been extended to higher dimensions [15], and successfully used to establish lower bounds for coloring unit disk and unit ball graphs [16]. Most recently, it has been used to study the parameterized complexity of Steiner Tree in planar graphs [17,18].…”
Section: Related Workmentioning
confidence: 99%